2017
DOI: 10.1007/s00300-017-2207-z
|View full text |Cite
|
Sign up to set email alerts
|

Lousy big guys: Lepidophthirus macrorhini infesting seals from Antarctica

Abstract: The present work represents a contribution to the ecology of a little known host parasite association, i.e. sucking lice and Antarctic seals. The information available regarding the health status of Antarctic seals is limited and little is known about the ecology and effect of parasites on these hosts. Particularly, data regarding Antarctic louse infestation are scarce. Therefore, the main goal of this study is to report the results of a survey of the louse infestation of Lepidophthirus macrorhini (Anoplura, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…When anaesthetization of seals was needed, the animals were immobilized following routine procedures (see details in Wheatley et al , ) by people from the Argentinean Antarctic Institute. Collecting lice from the flippers provides a reliable proxy for total louse load, and also reduces host handling time (Leonardi et al , ). Antarctic lice were collected in the northern sector of the Danco Coast and 25 de Mayo Island; lice from Australian sea lions and the northern fur seal were sampled by Rebecca McIntosh, Phillip Island Nature Parks, Australia, and Christine Fontaine, The Marine Mammal Center, U.S.A.; finally, lice from South American sea lions were obtained from the Parasitological Collection at Centro Nacional Patagónico, Puerto Madryn.…”
Section: Methodsmentioning
confidence: 99%
“…When anaesthetization of seals was needed, the animals were immobilized following routine procedures (see details in Wheatley et al , ) by people from the Argentinean Antarctic Institute. Collecting lice from the flippers provides a reliable proxy for total louse load, and also reduces host handling time (Leonardi et al , ). Antarctic lice were collected in the northern sector of the Danco Coast and 25 de Mayo Island; lice from Australian sea lions and the northern fur seal were sampled by Rebecca McIntosh, Phillip Island Nature Parks, Australia, and Christine Fontaine, The Marine Mammal Center, U.S.A.; finally, lice from South American sea lions were obtained from the Parasitological Collection at Centro Nacional Patagónico, Puerto Madryn.…”
Section: Methodsmentioning
confidence: 99%
“…The only evidence available suggesting that they do, comes from the finding in Antarctica of lice-infested adult seals. Given that infestation usually takes place as pups, lice on those adult seals have probably been living on their hosts for several months or years (Leonardi et al, 2018). Although suggestive, this is not definitive evidence that lice were already present when seals came ashore.…”
Section: Introductionmentioning
confidence: 93%
“…In a previous study, we found that on average almost 60% of the elephant seals from 25 de Mayo/King George Island were infested with lice (Leonardi et al ., 2018). Both the prevalence and the mean intensity are higher in pups and juveniles than adults (Leonardi et al ., 2018). The high presence of this lice species on elephant seals has also an epidemiological significance.…”
Section: Figmentioning
confidence: 99%
“…Lepidophthirus macrorhini Enderlein infests southern elephant seals during their entire life cycle (Murray & Nicholls, 1965). In a previous study, we found that on average almost 60% of the elephant seals from 25 de Mayo/King George Island were infested with lice (Leonardi et al ., 2018). Both the prevalence and the mean intensity are higher in pups and juveniles than adults (Leonardi et al ., 2018).…”
Section: Figmentioning
confidence: 99%